ANALISIS HUBUNGAN ANTARA EKSTENSIFIKASI WAJIB PAJAK, SURAT SETORAN PAJAK DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK (Students' Journal of Accounting and Banking, 2013)
Efforts made by the Directorate General of Taxation to meningkatkatkan state income taxation of the sector is to conduct searches or extensification taxpayers and improve tax compliance in submitting or report the amount of tax payable into the Tax Payment (SSP). The research objective to be achieved is to know how the relationship of the number of taxpayers, the Tax Payment (SSP), and taxpayer compliance to existing Revenue Tax Office Primary Palmerah Jakarta. In this study, samples were selected using purposive sampling technique that samples the criteria Compliant Taxpayers (timely submission of tax payable by the taxpayer) at the Jakarta Tax Office Primary Palmerah during the period from 2008 to 2011 on a monthly basis. Taxpayers who dutifully used as research data is Taxpayer Effective in 2008 to 2011. The type of data used in the form of secondary data obtained from the Tax Information System (SIP) Administrative Section of Taxation (TUP), SIP The Integrated Services (TPT), SIP's Data Processing and Information Section (SPDI), SIP's Directorate General of Taxation or Monitoring Payment of Tax reporting (MP3), Master File Tax Office Primary Palmerah in Jakarta from 2008 to 2011. Data analysis methods used were correlation analysis and hypothesis testing using Pearson Product Moment Correlation. These results indicate that the hypothesis is rejected, which means that the number of taxpayers have the relationship with the Revenue because the linearity of the relationship between the number of taxpayers with Revenue. While the second hypothesis is accepted, which means the Tax Payment Receipts Tax have the relationship with as there are relationships in the linearity between the Tax Payment Receipts Tax. The results of the third hypothesis is rejected, which means have the Taxpayer Compliance with Tax Filing relationship because there is linearity of the relationship between the Taxpayer Compliance with Tax Filing. Keywords: extensification Taxpayers, Tax Payment, Tax Compliance and Tax Filing.